2013
DOI: 10.1111/bjd.12049
|View full text |Cite
|
Sign up to set email alerts
|

STAT1 expression and activation is increased in lesional psoriatic skin

Abstract: This study demonstrates for the first time that the phosphorylation level of STAT1(Tyr701) and STAT1(Ser727) is increased in lesional psoriatic skin. In addition, specific signalling pathways leading to this phosphorylation have been identified. Together, our data indicate an important role of STAT1 in the pathogenesis of psoriasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
53
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(61 citation statements)
references
References 28 publications
3
53
0
2
Order By: Relevance
“…Aberrant IFN-g production and STAT1 activation are typically found in psoriatic lesions (33)(34)(35)(36). It is speculated that the IFN-g response is derived from Th1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant IFN-g production and STAT1 activation are typically found in psoriatic lesions (33)(34)(35)(36). It is speculated that the IFN-g response is derived from Th1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown both an increased expression of STAT1 in psoriatic skin and an increased STAT1 activity as measured by elevated phosphorylation levels of STAT1 (Tyr701) and STAT1(Ser727), which suggests that STAT1 plays a role in the pathogenesis of psoriasis [5,7,30]. Furthermore, STAT1 is known to play an essential role in the regulation of IFNα-induced genes by forming a heterotrimer with STAT2 and IRF9, a transcription factor complex known as IFN-stimulated gene factor 3 (ISGF3).…”
Section: Discussionmentioning
confidence: 99%
“…Advances in our understanding of the role of intracellular signaling in psoriatic inflammation have led to the recognition that many key psoriatic cytokines converge on and initiate intracellular signaling through specific pathways [1,3]. One such intracellular signaling pathway, which is believed to play a key role in the pathogenesis of psoriasis is the JAK/STAT signaling pathway [4][5][6][7]. Chang et al showed that a a1111111111 a1111111111 a1111111111 a1111111111 a1111111111 small molecule inhibitor of JAK3 markedly attenuated of skin lesions following 6 weeks of treatment in the CD18 mutant PL/J mice T cell-dependent psoriasis-form model [8].…”
Section: Introductionmentioning
confidence: 99%
“…Korábban Hald és munkatársai leírták az aktivált STAT1 kifejezôdését pikkelysömörös tünetes bôrben (17). Kutatócsoportunk megállapította, hogy a STAT1 aktív állapotban van jelen az egész-séges és a pikkelysömörös tüne-tes bôrben egyaránt, ellentétben a tünetmentes bôrrel, ahol jórészt inaktív formában található (18).…”
unclassified